(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the early functional outcome of cementless total hip replacement (THR) in patients with avascular necrosis head of femur. Methods: This descriptive study was conducted in Department of Orthopedic Surgery Unit I Services Hospital Lahore from 5th August 2018 to 10th September 2021. All adults patients of both gender with avascular necrosis of head of femur fulfilling the inclusion criteria were operated with cementless total hip replacement (THR). Post operative functional outcome at 3, 6 and 12 months was determined with Harris Hip Score(HHS) and compared with pre operative HHS. P value was calculated with paired t-test. P value < 0.05 was considered significant. HHS was graded excellent (90 to 100), good (80 to 90), fair (70 to 80) and poor (<70). Results: The total number of patients in our study was 83. Male patients were 64(75.3%) and female 19(22.4%). Mean age was 45.30 ± 9.12 years. Right sided THR was done in 45(52.9%) and left in 38(44.7%) patients. The pre-operatively mean HHS was 41.58 ± 10.36. Post operative mean HHS at 3, 6 and 12 months was 56.86 ± 9.14, 73.16 ± 8.21 and 85.55 ± 5.30 respectively (p < 0.05) Excellent functional outcome at one year was noted in 59 (71.08%) patients, good in 19 (22.89%) and fair in 5 (6.o2 %) patients. Conclusion: Excellent and good early functional outcome was achieved in majority of our patients who were treated with cementless total hip replacement for avascular necrosis head of femur in our series. We therefore recommend cementless total hip replacement as treatment of first choice in middle aged patients suffering from avascular necrosis of head of femur.